Submandibular ectopic thyroid tissue and concurrent thyroid hemiagenesis - Marie-Louise Uhre Hansen (Taylor & Francis Group, 2021)
Concurrent thyroid hemiagenesis and ectopic thyroid tissue are rare conditions and can challenge the clinical appearance. Only one other case story in the literature has described thyroid hemiagenesis and concurrent submandibular ectopic thyroid tissue. A 29-year-old female with an asymptomatic submandibular mass was referred to our clinic. Based on clinical investigation and ultrasound-guided fine-needle aspiration, we were not able to determine whether the neck mass was a cystic metastasis or ectopic thyroid tissue. Magnetic Resonance Imaging showed hemiagenesis of the right thyroid lobe. The neck mass was surgically removed, and the histopathology revealed thyroid tissue without malignancy. This case suggests that a thorough clinical evaluation with proper radiological imaging modalities is essential for the correct diagnosis. One should have in mind that ectopic thyroid tissue could be present outside the migration way of the thyroglossal duct and present as a submandibular neck mass.